Efficacy of pre and post AI administration of sterile Ceftriaxone sodium on conception rate in normal and repeat breeding crossbred cattle - MAHTO, DINESH; SINGH, M P; SINGH, BALRAJ; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
A total of77 normal and repeat breeder crossbred cows were treated with single dose sterile Ceftriaxone sodium. The Ceftriaxone sodium were infused intra-uterine 8-12 hr either pre or post-insemination during same estrus to evaluate the efficacy of the medicine on the conception rate of apparently normal and repeat breeding cows. In normal animals the conception rate percentages with pre & post A.I. Ceftriaxone sodium treatment were 53.84 and 57. I 4 as compared to 33.33 and 33.33%,respectively for control group. Similarly in repeat breeding cows, the conception rates were 50 and 50.14% with pre and post AI treatment as compared to 16.66 and 16.33%, respectively for control group. The differences were highly significant (P < 0.0 I).